The Maternal Early Warning Criteria: A Proposal From The National Partnership for Maternal Safety. Issue 3 (September 2015) - Mhyre, J.M.; D'Oria, R.; Hameed, A.B.; Lappen, J.R.; Holley, S.L.; Hunter, S.K.; Jones, R.L.; King, J.C.; D'Alton, M.E.
Abstract : ( Obstet Gynecol . 2014;124(4):782–786)